2007
DOI: 10.1055/s-2006-951724
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins from Cnidium monnieri and their Antiosteoporotic Activity

Abstract: Bioactivity-guided fractionation has led to the successful isolation of antiosteoporotic components, i. e., osthole, imperatorin and bergapten from an ethanolic extract of the fruits of Cnidium monnieri (L.) Cusson. Among them, osthole was determined as the major compound possessing antiosteoporotic activity. Further study showed that osthole not only promoted the proliferation and activity of alkaline phosphatase of osteoblasts in neonatal calvaria cultures, but also inhibited the bone resorption by decreasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 16 publications
1
48
1
1
Order By: Relevance
“…It has been reported that Osthole promoted the differentiation and maturation of osteoblasts [11][12][13][14]. However, our observations in this study seem controdictory to other reported findings, which are as follows: Firstly, the MSC proliferation was inhibited by Osthole.…”
Section: Cell Physiolcontrasting
confidence: 85%
See 1 more Smart Citation
“…It has been reported that Osthole promoted the differentiation and maturation of osteoblasts [11][12][13][14]. However, our observations in this study seem controdictory to other reported findings, which are as follows: Firstly, the MSC proliferation was inhibited by Osthole.…”
Section: Cell Physiolcontrasting
confidence: 85%
“…It had been widely reported that Osthole exerts a significant positive effect on osteoporosis treatment by promoting osteoblast differentiation and inhibiting bone resorption [10][11][12][13][14]. Interestingly, a recent study on biomaterial suggested that Osthole stimulation may enhance extracellular matrix (ECM) production and positively affect cell behavior in cell sheet engineering of jaw bone marrow mesenchymal stem cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Its chemical formula is C 15 H 16 O 3 . Osthole has been shown to exert a wide variety of biological effects, such as anti-seizure, anti-osteoporosis and anti-inflammation [10,11,12,13]. It has been well documented that osthole inhibits the growth and proliferation of various cancer cells through inducing apoptosis or cell cycle arrest [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effective concentration of bergapten (20-40 μmol/L) on LPS-induced bone loss in vitro was higher than that of it on osteoblast-like cells (such as UMR106, MG 63 and hFOB) (0.3-10 μmol/L) [10,11], indicating that bergapten preventing LPS-induced bone loss requires stronger concentrations than that of its stimulation of bone formation required in vitro. However, Zhang et al reported that bergapten had no effect on separated mature osteoclast and osteoclast resorption [17]. These different experimental results require further study.…”
Section: Discussionmentioning
confidence: 95%